2010
DOI: 10.1128/aem.00844-10
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate-Degrading Activity in Bifidobacterium animalis subsp. lactis : Impact of Acidic Conditions on the Transcriptional Levels of the Oxalyl Coenzyme A (CoA) Decarboxylase and Formyl-CoA Transferase Genes

Abstract: Oxalic acid occurs extensively in nature and plays diverse roles, especially in pathological processes. Due to its highly oxidizing effects, hyperabsorption or abnormal synthesis of oxalate can cause serious acute disorders in mammals and can be lethal in extreme cases. Intestinal oxalate-degrading bacteria could therefore be pivotal in maintaining oxalate homeostasis and reducing the risk of kidney stone development. In this study, the oxalate-degrading activities of 14 bifidobacterial strains were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 57 publications
3
66
0
Order By: Relevance
“…This activation effect was reported previously for oxalate metabolism in Bifidobacterium: preadaptation with subinhibitory concentrations of oxalate and lower pH resulted in increased oxc and frc mRNA concentrations (56). Stationary-phase cells (pH 5.5) exhibited a 4-fold increase in survival after incubation with 50 mM oxalate for 6 min.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This activation effect was reported previously for oxalate metabolism in Bifidobacterium: preadaptation with subinhibitory concentrations of oxalate and lower pH resulted in increased oxc and frc mRNA concentrations (56). Stationary-phase cells (pH 5.5) exhibited a 4-fold increase in survival after incubation with 50 mM oxalate for 6 min.…”
Section: Discussionmentioning
confidence: 58%
“…The yfdXWUVE operon in E. coli responds to the EvgAS regulatory system, and deletion of the operon results in reduced survival of wild-type K-12 MG1655 cells at pH 2.5 when EvgA is overexpressed in the cells (12), but these proteins are not linked to multidrug resistance in E. coli (55). Turroni et al previously reported a link to increased expression of oxc and frc mRNAs in bifidobacteria when cells are preadapted in oxalate and subsequently exposed to lower pH and higher oxalate concentrations (56). Previous microarray experiments have shown that yhjX, a putative oxalate:formate antiporter, is upregulated when cells undergo cytoplasmic acidification by treatment with benzoate (57).…”
mentioning
confidence: 99%
“…Thus, the pH of each gut region may be another important factor driving in vivo oxalate degradation and the densities of different species of oxalate-degrading bacteria. The genera Bifidobacterium and Lactobacillus degrade oxalate optimally at pH 4.5 and 5.5, respectively (35,44). However, optimal pH for oxalate-degrading activity within the Oxalobacter genus was reported as 6.4, after examination over the range of pH 5 to 8 (55).…”
Section: Discussionmentioning
confidence: 99%
“…One of the best-studied species is Oxalobacter formigenes, which requires oxalate as a carbon and energy source for growth (8). However, other oxalate-degrading bacteria include species from the genera Lactobacillus, Bifidobacterium, Streptococcus, Enterococcus, and others (11,(32)(33)(34)(35). The majority of studies investigating oxalate-degrading bacteria have been conducted on humans, lab rats, and agricultural systems.…”
mentioning
confidence: 99%
“…Previous research has focused on the role of individual taxa in oxalate degradation (7,20,29,37,38). However, several oxalate-degrading taxa have now been identified from the mammalian gut, and other taxa may be affected by oxalate in obscure ways (20,26,39,40). To address the gaps, we combined controlled laboratory diet trials, physiological assays, and microbial ecology to examine the taxonomic and functional response of the whole gut microbiota in a mammalian herbivore, N. albigula, which naturally consumes large amounts of oxalate in its diet, a simple compound that is metabolized exclusively by the gut microbiota (18,26).…”
Section: Discussionmentioning
confidence: 99%